Thermal Behavior of TiO2 (85%) / MWCNT (15%) - (CH2OH) 2 (50%) / H2O (50%) Hybrid Nanofluid under the Influence of Temperature and Volume Fraction Factors with Laboratory and Response Surface Methods - Mohammad Hemmat esfe (مجله مدل سازی در مهندسی)
In this study, for the first time, the thermal behavior of TiO2 (85%) / MWCNT (15%) - (CH2OH) 2 (50%) / H2O (50%) hybrid nanofluid thermal behavior is investigated. The thermal conductivity of the nanofluid is determined by KD2 PRO at fractional volumes of  φ =0.03% -0.6% and temperatures of T = 28 ° C-50 ° C. Nanoscale and nanoparticle structure validation are performed using transmission electron microscopy (TEM) and scanning (SEM) and X-ray diffraction (XRD) analysis tools. Experimental results of laboratory analyzes have shown that with increasing temperature and volume fraction, relative thermal conductivity (RTC) is increasing and the amount of this increase is more severe for volume fraction than temperature. The statistical results of experimental analysis showed that the minimum and maximum increase in thermal conductivity of nanofluid compared to the base fluid are 1.6% and 17.9%, respectively. The modeling of the response surface for the relative thermal conductivity of nanofluid showed that the values of R2 and Adj R2 were equal to 0.9882 and 0.9860, respectively, and the MOD value was between -1 and +1.